2021
DOI: 10.3390/antiox10020281
|View full text |Cite
|
Sign up to set email alerts
|

Human Placental NADPH Oxidase Mediates sFlt-1 and PlGF Secretion in Early Pregnancy: Exploration of the TGF-β1/p38 MAPK Pathways

Abstract: Preeclampsia, a hypertensive disorder occurring during pregnancy, is characterized by excessive oxidative stress and trophoblast dysfunction with dysregulation of soluble Fms-like tyrosine kinase 1 (sFlt-1) and placental growth factor (PlGF) production. Nicotinamide Adenine Dinucleotide Phosphate (NADPH) oxidase (Nox) is the major source of placental superoxide in early pregnancy and its activation with the subsequent formation of superoxide has been demonstrated for various agents including Transforming Growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…15 Among the potential cellular signaling pathways that could be impacted by ROS, the p38 MAPK pathway is a crucial candidate; it was shown to conduct signal transduction from the cell surface to the nucleus, [16][17][18] which would affect cellular survival, migration, proliferation, and differentiation. [19][20][21] Accumulated evidence indicates that the p38 MAPK pathway is one of the key signal pathways related to PE pathogenesis. 8,19,20 It has been demonstrated that nitration of phospho-p38 MAPK was higher in PE placentas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Among the potential cellular signaling pathways that could be impacted by ROS, the p38 MAPK pathway is a crucial candidate; it was shown to conduct signal transduction from the cell surface to the nucleus, [16][17][18] which would affect cellular survival, migration, proliferation, and differentiation. [19][20][21] Accumulated evidence indicates that the p38 MAPK pathway is one of the key signal pathways related to PE pathogenesis. 8,19,20 It has been demonstrated that nitration of phospho-p38 MAPK was higher in PE placentas.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Accumulated evidence indicates that the p38 MAPK pathway is one of the key signal pathways related to PE pathogenesis. 8,19,20 It has been demonstrated that nitration of phospho-p38 MAPK was higher in PE placentas. 22 Reduced phospho-p38 MAPK concentration and p38 MAPK catalytic activity were also found in placentas from PE cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitigation of NOX-induced oxidative stress in other cells also protects endothelial functions [61]. Given that placental NOX mediates sFlt-1 and placental growth factor secretion in first trimester chorionic villi [62], we could infer that the HCQ-mediated alleviation of preeclampsia and suppression of sFlt-1 and endothelin-1 signaling may involve NOX. Furthermore, HCQ and CQ function primarily by inhibiting lysosomal acidification, thus inhibiting autophagy in many cells [63].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another member detected is the subunit CYBA gene elevated in preeclampsia ( Gomes et al, 2012 ; Trifonova et al, 2014 ), suggesting that the NADPH oxidase activity plays a critical role during the oxidative stress observed in the pregnancy. Moreover, elevated NADPH oxidase activity can modulate the production of sFlt-1 and PlGF, suggesting the critical role of this activity in developing preeclampsia ( Hernandez et al, 2021 ).…”
Section: Hypertension and Pregnancymentioning
confidence: 99%